Identification of Individual Muscle Length Parameters from Measurements of Passive Joint Moment Around the Ankle Joint - Hisashi NAITO; Yasushi AKAZAWA; Ayu MIURA; Takeshi MATSUMOTO; Masao TANAKA (Journal of Biomechanical Science and Engineering, 2012)
In this study, we proposed a method for estimating muscle length parameters on an individual basis from measured data based on a musculo-skeletal structure with a Hill-type muscle model. Passive joint moments of the ankle were measured for 4 healthy subjects in two different knee positions, i.e., in knee flexion and extension, using manual measurement apparatus. Estimation of muscle length parameters based on measurement data from each subject was performed using a two-dimensional musculo-skeletal model of the lower limb with a Hill-type muscle model. Predicted passive joint moment properties using the estimated parameters were consistent with measured data. The estimated length parameters of muscles differed between subjects depending on their passive joint moment properties. These observations suggest that the proposed estimation method is available to identify muscle length parameters required for a quantification of ankle joint function and the musclo-skeletal model analyses on an individual basis.